Analisis Empiris Perilaku Lapse pada Nasabah Asuransi Jiwa di Indonesia - Kyi Zar Phyo Wai Hein; Jiengkham Keovilay; Wismoyo Adinegoro; Bangwon Ko (Jurnal Statistika dan Aplikasinya, 2020)
Understanding policyholder’s lapse behavior is important in managing insurers’ risk. Recently, numerous studies regarding lapse risk have been conducted in several countries. However, despite the market potential, none has been performed for Indonesia yet. Thus, in this paper, we investigate the determinants of lapse behavior for the Indonesian life insurance industry. Our empirical analysis considers two data sets from Indonesia Financial Service Authority and a private life insurance company using generalized linear model (GLM). In the first data set, we found a supporting evidence for emergency fund hypothesis. However, neither emergency fund hypothesis nor interest rate hypothesis was supported by the second data set. Instead, we found that other factors such as product type, premium payment frequency and policy age could affect policyholder’s lapse behavior more significantly.